2012
DOI: 10.1016/j.jretconser.2012.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Let the music play or not: The influence of background music on consumer behavior

Abstract: This study concerns the effect that music has on consumer behavior in two different retail contexts during regular opening hours. Two studies were conducted in a field setting with consumers (N = 550). Consumers were recruited to answer questions regarding behavioral measures, attitudes, and mood during days when background music was played. The conclusions from the two studies are that music affects consumer behavior, but also that the type of retail store and gender influences both the strength and direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(59 citation statements)
references
References 34 publications
2
56
0
1
Order By: Relevance
“…In the context of Mehrabian and Russell's PAD model, pleasure‐displeasure refers to a feeling state (such as good or happy); arousal refers to the extent to which one feels stimulated, alert, or active in an environment; and dominance refers to the extent to which one controls one's environment (Andersson, Kristensson, Wästlund & Gustafsson, ; Hines & Mehrabian, ). In a given situation, an individual's behavior is influenced by these domains and can be considered in terms of so‐called approach and avoidance behaviors.…”
Section: Mehrabian and Russell's Pad Modelmentioning
confidence: 99%
“…In the context of Mehrabian and Russell's PAD model, pleasure‐displeasure refers to a feeling state (such as good or happy); arousal refers to the extent to which one feels stimulated, alert, or active in an environment; and dominance refers to the extent to which one controls one's environment (Andersson, Kristensson, Wästlund & Gustafsson, ; Hines & Mehrabian, ). In a given situation, an individual's behavior is influenced by these domains and can be considered in terms of so‐called approach and avoidance behaviors.…”
Section: Mehrabian and Russell's Pad Modelmentioning
confidence: 99%
“…Prior research reported a moderating role for personal variables (e.g., demographics) and shopping orientations on customers' behavior in shopping environments (Andersson, Kristensson, Wästlund, & Gustafsson, 2012;Chang et al, 2011;Kaltcheva & Weitz, 2006). Thus, such personal and situational variables can be taken into consideration and applied to the hypothesized model as moderating variables in a future research.…”
Section: Limitations and Areas Of Future Researchmentioning
confidence: 99%
“…We anticipate that-in contrast to previous research-high levels of choice and control might be observed in public locations, depending on the device by which the music in question is accessed in those settings: it is necessary to consider how the music is encountered, with regard to devices and selection behaviors, in our understanding of listening episodes in different locations. Russell's (1974 -see also Andersson, Kristensson, Wästlund, &Gustafsson, 2012;Hines & Mehrabian, 1979) theory of environmental psychology asserts that people's interactions and interpretation of their contextual surroundings result from variations in three factors.…”
Section: Introductionmentioning
confidence: 99%